Performance of male bovines under intensive grazing of pasture and shrub legumes during dry period in Valle del Cauto, Cuba - Ledea, J. L.; Ray, J. V.; Cabrera, Y.; Nuviola, Y.; Benítez, Diocles (Cuban Journal of Agricultural Science, 2016)
The effect of improved pastures, combined and associated with shrub legumes, on the performance of Charolais males and ⅜ Charolais x ⅝ Zebu was studied in a representative area of Valle del Cauto during dry season. A completely randomized design and an intensive rotational grazing system were applied. Two grazing areas were established: 1) association of Megathyrsus + Leucaena and 2) combination of Megathyrsus + Cenchrus. Grazing was conducted during daylight hours, from 7:00 am to 5:00 pm, in paddocks of 0.28 ha with long periods of rotation. An amount of 10 animals were used in each treatment. The results showed that, in the association, the habit of grazing and lying varied according to genotype (P≥0.10). Only the habit of grazing herbaceous plants had significant effect (P ≤ 0.05). In the combination, all the activities showed significant effects for different confidence levels. Crossbred animals tended to spend less time consuming plants (P ≥ 0.10), while the time for resting was significantly superior compared to Charolais (P ≤ 0.05). Shrub component of associations had a compensatory effect on the performance of males in evaluation because there were no significant differences at a confidence level of 95%. The animals of both genotypes concentrated the highest time for grazing in the initial period of the morning and at the end of the afternoon. The applied grazing system maintained the performance pattern of meat-producer males during dry season. Key word: grasses, intensive grazing, associations, genotypes